Optimization study on amine absorption process - Pushpaa, Rajakumaran (2014)
Capturing CO2 produced from large scale combustion plants such as fossil fuel power plant is becoming more favourable and feasible. One of the most common methods used to capture CO2 is amine absorption process. An amine CO2 capture plant can capture as much as 90% of the CO2 emitted from the power plant and so has a real benefit for the environment. In this research, optimization is done to optimize the process operation of the absorber column. The parameters such as solvent flow rate, temperature of absorber, number of stages and height of absorber and absorber pressure were adjusted to obtain the optimum condition to maximize the CO2 removal. A process model was devôloped using the Aspen Plus® simulation and compared with the base case. This was followed by validating the base case data with the simulation data, so that the result obtain in the simulation is valid with less than 10% of error. From the result obtain, it shows that error percentage obtain is less than 10% with 0.45% of error percentage. It shows that the data obtain from the simulation is valid. This was followed by doing the optimization for amine absorption. Two types of optimization were done which is optimization for operating process condition and optimization for process condition with absorber design. Through the optimization process, the best case found is case 1 and case 6. The suitable optimization parameters are 0.25 mol CO2/mol IVIEA of lean loading, 30 wt% of MEA concentration, 1 bar of absorber pressure, 303K of flue gas and solvent temperature, 1100 kg/s of solvent flow rate, number of stages is 10, 14m of absorber height and 20m of absorber diameter.